A discrete-event simulation model with a collaborative and lean logistic approach application to a dairy industry (2024)
The research introduces a discrete-event simulation model that focuses on implementing a collaborative and lean logistic approach to enhance productivity and competitiveness within a supply chain. The model aims to improve processes in the supply chain by establishing more sustainable methods in production, transportation, and marketing activities. Additionally, a discrete-event simulation model has been created to represent a dairy supply chain and assess performance across various areas such as production activities, transportation, distribution, information systems, and indicators. The model utilizes Arena Simulation Software to depict processes, raw materials, suppliers, manufacturers, resources, products, and customers. It has been developed and validated through statistical comparison with real-world data. Furthermore, the current performance analysis has been computed, and scenarios have been defined to enhance infrastructure utilization, production capacity, collaboration, and lean logistic approaches. The study includes a case study of the dairy industry in Colombia to validate the model. The results indicate that collaborating with suppliers and implementing a new production line have significant benefits in strengthening the dairy sector, leading to improved production planning, the adoption of new technologies, increased incomes, and enhanced competitiveness in the industry.